2005
DOI: 10.1128/jvi.79.5.2666-2677.2005
|View full text |Cite
|
Sign up to set email alerts
|

Discerning an Effective Balance between Equine Infectious Anemia Virus Attenuation and Vaccine Efficacy

Abstract: Among the diverse experimental vaccines evaluated in various animal lentivirus models, live attenuated vaccines have proven to be the most effective, thus providing an important model for examining critical immune correlates of protective vaccine immunity. We previously reported that an experimental live attenuated vaccine for equine infectious anemia virus (EIAV), based on mutation of the viral S2 accessory gene, elicited protection from detectable infection by virulent virus challenge (F. Li et al., J. Virol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
7
30
0
1
Order By: Relevance
“…Twenty-four ponies of mixed age and gender (SI Table 3) were inoculated intramuscularly with two 10 3 TCID 50 doses, at a 4-week interval, of EIAV D9 . The inoculated ponies were monitored daily for clinical signs of EIA, and blood samples were taken at regular intervals for standard measurements of disease, virus replication, and host immune responses, as described (23)(24)(25)35). Six months after the second vaccination, the immunized ponies were randomly divided into three challenge groups, each consisting of eight animals (SI Table 3).…”
Section: Development Of Variant Challenge Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four ponies of mixed age and gender (SI Table 3) were inoculated intramuscularly with two 10 3 TCID 50 doses, at a 4-week interval, of EIAV D9 . The inoculated ponies were monitored daily for clinical signs of EIA, and blood samples were taken at regular intervals for standard measurements of disease, virus replication, and host immune responses, as described (23)(24)(25)35). Six months after the second vaccination, the immunized ponies were randomly divided into three challenge groups, each consisting of eight animals (SI Table 3).…”
Section: Development Of Variant Challenge Strainsmentioning
confidence: 99%
“…We have previously reported serial studies evaluating the efficacy of an attenuated EIAV proviral vaccine containing a mutation in the viral S2 accessory gene (EIAV D9 ) (23)(24)(25). The results of these studies indicate that horses inoculated with the EIAV D9 viral vaccine were 100% protected from disease by virulent EIAV challenge.…”
mentioning
confidence: 99%
“…Over the past 15 years we have evaluated a number of experimental EIAV vaccines based on inactivated whole virus, viral or recombinant envelope subunit vaccines, and various attenuated proviruses [1,2,[19][20][21][22]. The results of these vaccine trials demonstrate a remarkable breadth of efficacy, ranging from protection from detectable infection and/or disease to severe enhancement of EIAV replication and disease.…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractWe previously reported that an experimental live-attenuated equine infectious anemia virus (EIAV) vaccine, containing a mutated S2 accessory gene, provided protection from disease and detectable infection after virulent virus (EIAV PV ) challenge [1,2]. To determine if attenuated EIAV vaccines actually prevent persistent infection by challenge virus, we employed a 14-day dexamethasone treatment of vaccinated horses post-challenge to suppress host immunity and amplify replication levels of any infecting EIAV.
…”
mentioning
confidence: 99%
“…Algunos autores han reportado previamente esta coinfección viral, con resultados contrastantes en los cuales se ha evidenciado in vivo que la infección por el HVE puede afectar la respuesta inmune al VAIE (30). Otros autores demostraron que la presencia de anticuerpos positivos para herpesvirus no modifican la tasa de replicación del VAIE (31).…”
Section: Discussionunclassified